2013
DOI: 10.3810/pgm.2013.05.2663
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Dipeptidyl Peptidase-4 Inhibitor Linagliptin

Abstract: Linagliptin is a xanthine-based, oral DPP-4 inhibitor that has been approved in the United States and Europe. It has been evaluated extensively in clinical trials, and results in improved glycemic control when used as monotherapy, initial combination therapy with metformin or pioglitazone, add-on therapy to metformin and/or a sulfonylurea, or add-on therapy to basal insulin (with or without oral antidiabetic drugs). Consistent with other members of its class, the benefits of linagliptin also include a low risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Because of the progressive decline of b-cell function in Type 2 diabetes, most patients eventually require intensification of anti-diabetes therapy to maintain glycaemic control [1]. Given the complementary mechanisms of action of linagliptin, metformin and pioglitazone, triple combination therapy with these oral anti-hyperglycaemic drugs is theoretically an attractive treatment strategy [7,[23][24][25]. These results support the use of this combination as an effective third-line therapeutic option when dual therapy with metformin and pioglitazone fails.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Because of the progressive decline of b-cell function in Type 2 diabetes, most patients eventually require intensification of anti-diabetes therapy to maintain glycaemic control [1]. Given the complementary mechanisms of action of linagliptin, metformin and pioglitazone, triple combination therapy with these oral anti-hyperglycaemic drugs is theoretically an attractive treatment strategy [7,[23][24][25]. These results support the use of this combination as an effective third-line therapeutic option when dual therapy with metformin and pioglitazone fails.…”
Section: Discussionmentioning
confidence: 88%
“…The addition of a dipeptidyl peptidase‐4 (DPP‐4) inhibitor to this combination is an attractive treatment option, offering an additional complementary mechanism of action. DPP‐4 inhibitors increase active levels of glucagon‐like peptide 1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide, increasing insulin secretion and inhibiting glucagon secretion . The increase in GLP‐1 may also improve β‐cell function .…”
Section: Introductionmentioning
confidence: 99%
“…The Phase 3 program also demonstrated that linagliptin treatment was weight neutral and that the rate of serious adverse events (AEs) across all trials was low 17,18 . The risk of hypoglycemia with linagliptin is low, except when used in combination with a sulfonylurea or insulin 17,18,25 .…”
Section: Linagliptinmentioning
confidence: 97%
“…The risk of hypoglycemia with linagliptin is low, except when used in combination with a sulfonylurea or insulin 17,18,25 .…”
Section: Linagliptinmentioning
confidence: 99%
“…Metformin reduces fracture risk and protects bone health as per several clinical, preclinical, and in-vitro studies (41)(42)(43)(44)(45)(46)(47)(48). Currently, linagliptin is clinically prescribed either as a monotherapy in metformin intolerant patients or as a combination with metformin for better glycemic control (35,49,50). However, the role of the combination of linagliptin and metformin in type 2 diabetesassociated osteoporosis has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%